O06.5 Do treatment rates suffer in a low-touch screening model? new york city sexual health clinics, 2017–2018. (14th July 2019) - Jamison, Kelly; Pathela, Preeti; Blank, Susan; Schillinger, Julia
Abstract : Background: Low-touch (i.e. limited staff interaction) models for asymptomatic STI screening have been widely adopted in sexual health clinics (SHCs) and can improve clinic flow and patients' experience. In New York City SHCs, asymptomatic patients who do not report contact to STI screen for urogenital and extragenital bacterial STI using self-collected specimens without a medical encounter. We evaluated treatment rates for Neisseria gonorrhea (GC) cases detected by this low-touch, self-screening model. Methods: We identified men-who-have-sex-with-men (MSM) who tested GC-positive by urogenital or extragenital nucleic acid amplification testing at any visit type (self-screening or standard clinician) during 01/2017–06/2018. Among GC cases that had not been presumptively treated, we assessed the number and percent of asymptomatic cases that returned for treatment within 30 days, and HIV pre-exposure prophylaxis (PrEP) use. We used Kaplan-Meier methods to examine time-to-treatment by visit type. Results: Of 3, 944 GC cases, 2, 268 were presumptively treated and 1, 676 needed to return for treatment. Among returning patients, median time-to-treatment was 6 days (IQR: 4–8). Cases detected at self-screening visits had shorter time-to-treatment than those detected at standard visits (p=0.008). Among GC cases detected at self-screening visits, 85% (454/534) were treated < 14 days, and 90% (480/534) < 30 days, compared to 80% (917/1, 142) of standard cases treated < 14 days, and 87% (991/1, 142) < 30 days after the visit. HIV-negative men with rectal GC had shorter time-to-treatment following self-screening versus standard visits (p=0.007), and fewer remained untreated by 30 days (self-screening: 7% versus standard: 13%; p=0.02). Of 76 HIV-negative men with rectal GC who were lost to follow-up, 22 (29%) were documented to be taking HIV PrEP at time of testing/screening. Conclusion: Among HIV-negative MSM with rectal GC, a group for whom delayed treatment may increase risk for HIV acquisition, a low-touch/self-screening model results in overall treatment rates and times-to-treatment that compare favorably to a standard clinician model. Disclosure: No significant relationships.